Psychology, environment and climate change: foregrounding justice (part one) - Barnes, Brendon R.; Barnwell, Garret; Hendricks, Lynn (PINS-Psychology in Society, 2022)
We are living through unprecedented global heating, environmental pollution, chemical toxicity, biodiversity loss, extractivism, environmental militarisation, exclusion of marginalised people in decision-making processes, violence directed at environmental defenders and limits to public engagement, to name a few issues (IPCC, 2022, Menton & Le Billon, 2021, Noyes et al., 2009, Sealey-Huggins, 2018). While psychologists are paying increasing attention to environmental degradation and climate change (Bailey, Pool & James, 2021, Wainwright and Mitchell, 2021), the discipline has been somewhat slow to address the political and structural dimensions that underpin those issues. Importantly, mainstream psychological scholarship has neglected marginalised people who are disproportionately affected and underrepresented in environmental and climate scholarship and practice.